Global Governance sebagai Agenda Penelitian dalam Studi Hubungan Internasional - Muhadi Sugiono (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2004)
Global governance has entered intellectual debates in the International Relations since early 1990s. What global governance exactly means, however, is still very much debatable. Without ignoring the contentious nature and without aspiring to offer alternative definition of the concept, this article seeks to present ways in which global governance can be best understood. As such, global governance can be seen as a normative project, an idealised global political order to be achieved in order to tame globalization. This view of global governance represents mostly, but not merely, that of practitioners of international relations. At the same time, global governance can also be seen as descriptive and analytical frameworks which can be employed by students of International Relations. While it does not reflects an epistemological breakthrough in the study of international relations, global governance offers a challenging and promising research agenda.